Utilization of coal bottom ash as raw material for production of ceramic floor tiles - Namkane K. (2017)
© 2016, Springer-Verlag Berlin Heidelberg. The aim of this research was to produce ceramic floor tiles using coal bottom ash (CBA), which is a no-value waste from coal power plants, as the raw material. CBA was first mixed with clay at various compositions to determine the proper ratio. Shaping through the dry pressing and single-firing route was chosen for this study. The properties of these ceramic tiles were investigated. Classification of these ceramic tiles has been adopted within the international standard, ISO 13006. Investigation of the optimum conditions for producing this product showed that coal bottom ash content combined with clay in the batch samples should not be more than 40 wt% and that the temperature for sintering was 1175 °C. The addition of sand could reduce linear shrinkage and increase the whiteness of the fired body. The products had less than 3 % water absorption, which is the property in the requirement of group BIb, but flexural strength was in the range of 22–30 MPa, which is the property in the requirement of group BIIa. The results obtained indicate that coal bottom ash when mixed with traditional raw materials has potential as a raw material for production of ceramic floor tiles.